Návrh počítačové sítě na Gymnáziu a SOŠ - Konečný, Jan (Vysoké učení technické v Brně. Fakulta podnikatelská, 2008)
Cílem práce je vytvořit návrh počítačové sítě pro Gymnázium a SOŠ. Popisuje se zde výběr typů síťových prvků, jejich množství a umístění, dále je zde také navrhnut rozvod síťové infrastruktury v budově školy.

The aim of work is formed project of computer´s network for Gymnasium and SOŠ. There is described selection types of network components, their quantities and location and there is also projected network infrastructure distribution at school building.
Design of the computer network at the Gymnazium a SOS
Keywords: Počítačová síť; strukturovaná kabeláž; Ethernet; datový rozvaděč; patch panel; Computer network; structured cableway; Ethernet; data switchboard; patch panel